Unraveling the Metamorphosis of Economic Education: A Comprehensive Exploration of the Dynamics of Distance Learning - Yati, Yati; Siswanto, Romi; Kadarisman, Kadarisman; Jaya, Fitra; Sucipto, Sucipto; Hutabarat, Zuhri Saputra (IKIP PGRI Bojonegoro, 2025)
This research aims to examine the effectiveness of distance learning in economics education, with a focus on student experiences and perceptions. Through a qualitative approach, this research explores the quality of learning materials, flexibility, interaction, use of technology, and academic support in the distance learning context. Findings indicated that although students appreciated the flexibility and accessibility of distance learning, they identified challenges in engagement and academic support. This research suggests the need for more interactive learning materials, improved technological infrastructure, and strategies that facilitate interaction and more effective academic support. These findings contribute to the understanding of distance learning in Indonesia and provide recommendations for educational practitioners and researchers.